Availability and Use of ICT in Schools in Delhi - Siddique, M. A.; Abraham, J. (INDIAN EDUCATIONAL REVIEW, 2011)
To study the availability of hardware and software facility in schools in Delhi. (ii) To study the extent of use of technologies in different type of schools as evident from competencies in students. (iii) To study the impact of ICT on students. (iv) To study the extent of training in computers received by the teachers of Delhi.